2018
DOI: 10.5753/jis.2018.704
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Interaction for Augmentative and Alternative Communication: a Systematic Mapping

Abstract: Verbal communication is essential for socialization, meaning construction and knowledge sharing in a society. When verbal communication does not occur naturally because of constraints in people’s and environments capabilities, it is necessary to design alternative means. Augmentative and Alternative Communication (AAC) aims to complement or replace speech to compensate difficulties of verbal expression. AAC systems can provide technological support for people with speech disorders, assisting in the inclusion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Although various mapping studies and systematic reviews investigate the effect of high-tech AAC on users' communication [Ascari et al 2018, Aydin and Diken 2020, Dada et al 2022, we found no similar research regarding the use of pictogram prediction in AAC systems, and its effect in users' communication. In this paper, we systematically map the literature searching for the strategies used for pictogram prediction in high-tech AAC systems and the methods used to evaluate them.…”
Section: Introductionmentioning
confidence: 58%
“…Although various mapping studies and systematic reviews investigate the effect of high-tech AAC on users' communication [Ascari et al 2018, Aydin and Diken 2020, Dada et al 2022, we found no similar research regarding the use of pictogram prediction in AAC systems, and its effect in users' communication. In this paper, we systematically map the literature searching for the strategies used for pictogram prediction in high-tech AAC systems and the methods used to evaluate them.…”
Section: Introductionmentioning
confidence: 58%
“…Technical AAC solutions for symbol-based communication range from simple concatenation of symbols for needs-based, functional communication with small vocabularies to complex (commercial) systems (see, e.g., Lancioni et al (2019) for a detailed survey). Currently, technical AAC solutions are evolving rapidly and are increasingly available on mainstream devices like smartphones and tablets (Light and McNaughton, 2012;Ascari et al, 2018;Farzana et al, 2021).…”
Section: Symbol-based Writing Systemsmentioning
confidence: 99%
“…La CAA incorpora una amplia gama de procesos que aumentan, complementan o reemplazan el habla de individuos con necesidades complejas de comunicación (Cook & Polgar, 2014;Schultz Ascari et al, 2018). En el amplio contexto del habla y el lenguaje, el habla a menudo se asocia con los movimientos motores responsables de la producción de palabras habladas, mientras que el lenguaje se asocia con las habilidades de procesamiento cognitivo de la comunicación.…”
Section: Planteamiento Del Problemaunclassified